2016
DOI: 10.1097/md.0000000000004705
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from surgical outcome for intracranial meningioma involving major venous sinus

Abstract: Intracranial meningiomas involving the major venous sinus (MVS) pose several complication risks upon performing radical resection. Some surgeons consider MVS invasion a contraindication for a complete resection of meningioma, and others suggest total resection followed by venous reconstruction. The aim of the study was to analyze our surgical results and discuss management strategy for intracranial meningiomas involving the MVS. Between 1993 and 2011, 107 patients with intracranial meningiomas involving MVS un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Their results showed an increase in the health-related QOL score from 73.9 to 84.9, which means that there is a significant improvement in their QOL and, thus, a favorable outcome. Further studies by Kalkanis et al and other authors support this attitude, while also observing QOL improvement after meningioma surgery [ 1 , 17 – 19 ]. When regarding the relationship of the Karnofsky indices to each other, binary logistic regression indicated a negative association between K1 and Kd, which was confirmed by Spearman’s correlation.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Their results showed an increase in the health-related QOL score from 73.9 to 84.9, which means that there is a significant improvement in their QOL and, thus, a favorable outcome. Further studies by Kalkanis et al and other authors support this attitude, while also observing QOL improvement after meningioma surgery [ 1 , 17 – 19 ]. When regarding the relationship of the Karnofsky indices to each other, binary logistic regression indicated a negative association between K1 and Kd, which was confirmed by Spearman’s correlation.…”
Section: Resultsmentioning
confidence: 82%
“…Markovic et al investigated the influence of peritumoral edema on the prognosis of morbidity and postoperative complications referring to 78 patients with supratentorial meningiomas treated surgically[ 37 ]. They determined that the outcome was significantly better in cases without than in patients with peritumoral edema, but there is no clear consensus in the literature [ 1 , 27 ]. This study, however, identified a connection between the occurrence of peritumoral edema or mass effects and an improved Kd score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while Simpson grade 1 resection would be desirable if recurrence was the only consideration, in real life, there are many other important considerations, not least widely published morbidity related to radical resection of meningiomas invading venous sinuses. [ 45 , 46 ] Indeed some authors propose that use of stereotactic radiosurgery following incomplete resection of parasagittal meningiomas reduces recurrence rates to those seen with Simpson grade 1 resections. [ 47 ] While we have notinvestgated this directly our data does not support pursuing radical resection in parafalcine/parasagittal meningiomas at the expense of morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Moon-Soo Han и соавт. [19] проанализировали результаты лечения 107 пациентов с ПСМ и выявили существенную зависимость вероятности рецидива от степени инвазии ВСС менингиомой. При этом радикальность операции по шкале Симпсона, гистологический тип, размер опухоли и перитуморозный отек статистически значимого влияния на вероятность рецидива не оказывали.…”
Section: Discussionunclassified